Strategi Layanan Bimbingan dan Konseling Bagi Korban Bencana : Pendekatan Trauma Healing dan Dukungan Psikososial - Elvina, Siska Novra; Fitri, Wanda (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
Indonesia is one of the world's most disaster-prone countries, with a high frequency of earthquakes, tsunamis, floods, and volcanic eruptions. This study aims to analyze guidance and counseling services based on trauma recovery and psychosocial support as an integrated method in the recovery process for disaster victims. The methodology applied in this study is a qualitative approach through desk research, evaluating literature from various primary and secondary sources. The research findings indicate that trauma recovery has proven effective in reducing psychological symptoms, while psychosocial support plays a crucial role in increasing individual resilience through social networks. Combining these two approaches can result in more comprehensive counseling services, encompassing personal, social, and spiritual elements. This study also identified various implementation challenges, such as limited human resources, geographic accessibility, social stigma, and lack of funding. Therefore, strategic solutions are needed that include training trauma counselors, utilizing telecounseling technology, and cross-sector collaboration. This research provides theoretical and practical contributions to the development of more effective and sustainable post-disaster counseling services. Keywords: guidance and counseling, disaster, trauma healing, psychosocial support, resilience